The journey to diagnosis of wild-type transthyretin-mediated (ATTRwt) amyloidosis: a path with multisystem involvement - Chafic Karam; Colleen Moffit; Catherine Summers; Madeline P. Merkel; Fran M. Kochman; Laure Weijers; Mathilde Puls; Marieke Schurer; Emily Jones; Nicola Mason; Muriel Finkel; Paula Schmitt; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Wild-type and hereditary transthyretin-mediated amyloidosis (ATTRwt and ATTRv amyloidosis, respectively) are progressive, fatal diseases with a broad range of clinical presentations and multisystem effects. Despite having a higher prevalence, ATTRwt amyloidosis is less well characterized due to its non-hereditary nature, and its relatively poorer disease awareness delays diagnosis. Understanding of its natural history has evolved in recent years, but this is largely based on physician-collected data rather than patients’ reports of their own experiences. A mixed methods approach was used to evaluate how the healthcare journeys of patients with ATTRv and ATTRwt amyloidosis compare. Methods A quantitative survey was administered to US-patients diagnosed with both ATTRwt amyloidosis and ATTRv amyloidosis identified through a patient support group. Subsequent in-depth interviews with participants with ATTRwt amyloidosis were conducted. Quantitative data with related qualitative quotes from patients were produced to characterize their paths to diagnosis and the disease burden experienced. Results A total of 47 respondents completed the survey (ATTRv, n = 20 and ATTRwt, n = 27) and a total of 14 survey respondents with ATTRwt amyloidosis were interviewed. Survey results reported a high disease burden for patients with both conditions, with patients with ATTRwt amyloidosis reporting more diagnoses and procedures prior to their final diagnosis. Interviews with participants with ATTRwt amyloidosis revealed that patients face a high symptomatic burden of disease. Diagnosis was often delayed due to three key factors: (1) early signs of ATTRwt amyloidosis were often assumed to be related to old age; (2) many medical specialists working in silos were involved in participants’ diagnostic; and (3) there was a general lack of disease awareness. Early indicators such as carpal tunnel syndrome were often overlooked. Participants were typically diagnosed after the disease had progressed to include severe cardiac symptoms such as atrial fibrillation and severe shortness of breath. Sleep apnoea was also reported by a number of participants, with a considerable impact on quality of life. Conclusions Our study provides insight into the overall impact of the patient journey on their quality of life and demonstrates how increased awareness of ATTRwt amyloidosis and more coordinated engagement with physicians could reduce the time to diagnosis.